An argument with God: Bhagavannindā in the Mahābhārata tradition - Sharma, DV (2021)
This thesis tells two stories—one of how the god Kṛṣṇa’s humanity and divinity came to be defined in the aftermath of the Mahābhārata’s composition. Another is how the Mahābhārata itself was taken seriously as a Vaiṣṇava text in its reception history. Through a close reading of Sanskrit commentaries, polemics, and narrative texts, I examine how these texts—and the religious communities that composed them—developed a theology of a fully-divine Kṛṣṇa in late-medieval and early modern South India, and how the Mahābhārata became explicitly Vaiṣṇava through the reinterpretation of the god Kṛṣṇa’s humanity. With the proliferation of Sanskrit commentaries and treatises on the overall meaning of the epic in the medieval and early modern period, clarifying Kṛṣṇa’s role becomes an explicit part of explaining the Sanskrit epic. The theology of a fully-divine human incarnation of Viṣṇu required a justification of the conduct, censures, and diminishment of Kṛṣṇa in the Mahābhārata, and a clarification of his role. This included justifying his conduct, explaining why he is rebuked constantly, and reinterpreting his ‘human’ death and his worship of other gods.